The Janet Frame case – traps of autobiographism Triumph of autobiography - Modrzejewska-Świgulska, Monika; Agnieszka Gralak, Łukasz Zieliński (Biograficzne badania nad twórczością. Teoria i empiria, 2016)
The article is an analysis of a three-volume autobiography of a New Zealand writer, Janet Frame (1924–2004). A literary description of life of a writer not well-known in Poland is taken as an example of an extraordinary triumph of literature. Thanks to Frame’s talent it becomes possible to transform the social stigma that is connected with schizophrenia into her individual mark of artistic independence. However, Frame’s trilogy is now read also as an example of a broader problem: mutual relations between social norms and human creativity.